Characterization of Wnt genes in Argopecten scallops and their involvement in response to different temperature stresses in “Bohai Red” scallops - Wang, Caihui; Lei, Shuhua; Chen, Min; Ning, Junhao; Lu, Xia; Zhang, Jinsheng; Liu, Bo; Wang, Chunde (Journal of oceanology and limnology, 2023)
As “Bohai Red” scallops were originated from the hybrids between the Peruvian scallop ( Argopecten purpuratus ) and the bay scallop ( Argopecten irradians ) northern subspecies ( Argopecten irradians irradians ). Twelve Wnt members were identified from the two subspecies of bay scallop, and 13 Wnt genes were found in the genome of the Peruvian scallop. Protein structure analyses showed that most Wnt genes poses all 5 conserved motifs except Wnt1, Wnt2, Wnt6 , and Wnt9 in the bay scallops and Wnt2 and Wnt9 in the Peruvian scallop. Unexpectedly, Wnt8 gene was present while Wnt3 was absent in both the bay scallops and the Peruvian scallop. Phylogenetic analysis revealed that Wnt3 might have disappeared in the early evolution of mollusks. The expression profile of Wnt genes in the “Bohai Red” exposed to different temperatures was examined by qRT-PCR. Results show that expression of Wnt genes responded differentially to temperature changes. The Wnt genes such as Wnt1, Wnt6, Wnt7, Wnt11 , and WntA that responded slowly to low and high temperature stresses may be related to the maintenance of basic homeostasis. Other Wnt genes such as Wnt4, Wnt9, Wnt5 , and Wnt2 that responded rapidly to low temperature may play an important role in organismal protection against low temperature stress. And yet some Wnt genes including Wnt10, Wnt16 , and Wnt8 that responded quickly to high temperature stress may play key roles in response to high temperature stress. The results provide new insights into the evolution and function of Wnt genes in bivalves and eventually benefit culture of “Bohai Red” scallops.